Nepal : Report on the Observance of Standards and Codes (ROSC), Corporate Governance Country Assessment - World Bank (Washington, DC, 2012)
This report assesses Nepal's corporate governance policy framework, enforcement, and compliance practices. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Nepal. Awareness of the importance of corporate governance is growing. The central bank has introduced higher corporate governance standards for banks and other financial companies as part of a wider program of financial sector reform. Accounting and auditing standards are being developed. And a number of draft laws have been prepared that if passed and implemented should deepen and accelerate the reform process. The legal framework contains large and significant gaps. Critical institutions, including the securities board and company registrar, have little resources or authority. Most importantly, political uncertainty and the current security situation have weakened the economy and delayed the passage of draft legislation. Passing the current draft legislation is the critical next step. Overall, reform should seek to enhance key institutions, better protect shareholder rights, enhance transparency, and increase the effectiveness of boards. This will require a combination of legislative change, action by regulators and the public sector, and can be aided by targeted technical assistance.